The Transformative Impact of Innovative Work Behavior on Entrepreneurial Orientation and Organizational Performance - Anak Agung Ketut, Sriasih; I Made Hedy , Wartana; I Ketut , Yudana Adi; I Putu Bagus , Suthanaya (Publisher Cv. Inara, 2025)
Innovative work behavior, entrepreneurial orientation, and organizational performance are central to achieving competitive advantage and resilience in dynamic business environments. This study examines how innovative work behavior affects organizational performance within firms. The study also explores the critical role of entrepreneurial orientation as both a direct influence on organizational performance and as a mediator in the relationship between innovative work behavior and organizational performance. This research was conducted on small & medium enterprise in the Province of Bali, Indonesia. Data were collected by 396 questionnaires from managers representing small & medium enterprise as research respondents and analysis was carried out using structural equation modelling. Results indicate that innovative work behavior has a positive impact on organizational performance, though its effect is enhanced significantly when mediated by entrepreneurial orientation. Specifically, the analysis reveals a strong relationship between innovative work behavior and entrepreneurial orientation, demonstrating that organizations fostering innovative behaviors are more likely to develop a proactive and risk-oriented culture. entrepreneurial orientation, in turn, shows a substantial direct positive effect on organizational performance, confirming its role as a critical driver of organizational success. Importantly, the mediation analysis suggests that entrepreneurial orientation partially mediates the relationship between innovative work behavior and organizational performance, channeling innovation efforts toward strategic objectives for optimal performance gains. The study contributes to the fields of innovation and entrepreneurship by elucidating the synergistic relationship between innovative work behavior and entrepreneurial orientation in driving organizational performance. The findings highlight the importance of fostering an entrepreneurial organizational culture that directs individual innovation toward strategic outcomes. This research provides valuable implications for organizational leaders aiming to enhance performance through integrated innovation and entrepreneurship strategies, and it sets the stage for future research exploring additional mediating factors and varied industry applications.